The Riddle of the Bark and the "Bite" - Dow Chemical Company (1951)
Black and white print advertisement for Esteron 245 and other weed, brush, and grass control chemicals manufactured and sold by the Dow Chemical Company. The advertisement features an illustrated depiction of a farmer spraying the toxicant over a sapling, with accompanying text detailing the use of Esteron 245 in basal bark treatment. This advertisement appeared on page 132 of the October 1951 edition of Country Gentleman.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Advertising; Advertising, Industrial; Agricultural chemicals; Agricultural chemicals industry; Herbicides